PERAN BUMDES ISTIQOMAH DALAM MENINGKATKAN PAD DAN KESEJAHTERAAN MASYARAKAT DESA BUKIT KEMUNING MERSAM - Novella Febiana; A.A. Miftah; Dessy Anggraini (Jurnal Riset Manajemen dan Akuntansi, 2023)
BUMDes Istiqomah was founded at the end of 2017. BUMDes has several businesses, namely credit units, gas, office stationery, buildings, and Pamsimas. This study aims to determine the role of Istiqomah BUMDes in increasing village original income and community welfare. This research is included in the type of qualitative research, data collection techniques are carried out by interviews, observation and documentation. The results of the study show that BUMDes Istiqomah can already be said to have a role but not optimally. The role of BUMDes can be seen from the units that can help and facilitate the community. BUMDes Istiqomah has also contributed to the village's original income even though the funds provided are still relatively low. The people of Bukit Kemuning Village can also be said to be prosperous, but this is purely from the business they are running, not entirely because of the BUMDes. This is because there are still many obstacles faced by BUMDes such as management and management that have not been maximized, lack of support from the village government, limited capital, low community participation in BUMDes businesses. The management of Istiqomah BUMDes according to researchers is in accordance with Islamic Economics. The business units it runs have helped and made it easier for the community to meet their needs. This is in accordance with Islamic economic principles, namely for the benefit of the people, the business carried out by BUMDes Istiqomah is in accordance with Islamic principles, even though the role given is not maximized.